Efeito do diodo emissor de luz (LED) de alta potência sobre a retina de ratos - Araújo, Marcela Emílio de (2018)
Introduction: The evolution of light curing units (LCU) in terms of potency and consequent reduction of clinical time have been shown to be of great value to orthodontists, regarding the routine of brackets bonding. However, there is a lack in the literature regarding the effect of these devices on the operator and/or patient retina, as both may receive indirect reflected light during procedures. Aims: Evaluate the effect of the use of a high potency light emitting diodebased device (LED) in the retina of Wistar rats. Material and Methods: Six Wistar rats were used and their ocular structures considered objects of the study. During the photostimulation of each animal, the right eye, established as the control sample, was covered with a removable PVC tampon, as the contralateral eye - experimental sample - was exposed to high potency LED light, 3200mW/cm2 (Valo Ortho - Ultradent) for 144 seconds, at the distance of 30cm. Animals were exposed to LED light three times per day, aiming to induce possible acute inflammatory alterations in retina. Seven days after the first photostimulation, all rats were anesthetized and then euthanized for posterior eye removal and histological processing. The histological slides were scanned using a camera connected to an optical microscope and their images analyzed for the measurement of histomorphological and stereological parameters of the retina. Results: A statistically significant raise was found in the total volume of retina and in the following layers: ganglion cells layer (GCL), outer nuclear layer (ONL), inner nuclear layer (INL) and extension of cone and rods (ECR) in the experimental group. Regarding density, no statistically significant difference was observed. However, the nuclear area of the cells raised significantly in all layers analyzed after high potency LED exposure. Besides that, hyperchromic cells suggestive of pyknosis were found. Conclusions: Despite the short and acute protocol of eye exposure to high potency LED, a significant alteration was found, especially in the metabolic activity of photosensitive and neuronal cells. These results emphasize the importance of using eye protection during the use of these devices.